Buzan, Barry y Lawson, George (2015). The global transformation. History, modernity and the making of international relations. Cambridge: Cambridge University Press - Corvalán, Facundo Gustavo (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto Multidisciplinario de Estudios Sociales Contemporáneos, 2016)

(untitled)
Fil: Corvalán, Facundo Gustavo . Universidad Nacional de Cuyo